Paratesticular solitary fibrous tumour: Case report and review of the literature - Akpolat, Nusret; Ardiço?lu, Arslan; Yahşi, Seyfettin; Onur, A. Rahmi (My University, 2003)
[Abstract Not Available]
Keywords: Paratestis; Solitary Fibrous tumour